(untitled) (Nigerian Journal of Technology, 2022)
A brief history of quality control and productivity is hereby traced. The cultural implications of quality Circle management technique are discussed in its relationship with productivity. The paper emphasizes the role of total preventive maintenance in productivity and quality improvements. In all these the workforce holds the key, the only key, to success in the creation of wealth and so should be made sound in body (and spirit) through appropriate training and motivation.